(untitled) - Choi, Wook (New York, 2012)
Included to illustrate the amount of dedication, focus, and creative talent you should expect to exhibit in your own pieces to gain admission to and win scholarships from the schools featured in this book.
Keywords: Art,Nghệ thuật; Study and teaching (Higher),Học tập và giảng dạy (Cao hơn)